Intentional Islanding Solution Based on Modified Discrete Particle Swarm Optimization Technique - Saharuddin N.Z.; Abidin I.Z.; Bin Mokhlis H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Distributed power generation; Electric lines; Electric load flow; Electric load shedding; Electric power transmission; Particle swarm optimization (PSO); Discrete particle swarm optimization; Intentional islanding; MDPSO technique; Minimal power; Objective functions; Power flow analysis; Power system blackout; Steady state stability; Heuristic methods